Horner's syndrome: An unusual presentation of metastatic disease in breast cancer. (December 2015) - Vitale, Maria Giuseppa; Riccardi, Ferdinando; Carrillo, Giovanna; Trunfio, Martino; Mocerino, Carmela; Minelli, Salvatore; Barbato, Carmela; Ambrosio, Francesca; Cartenì, Giacomo
Horner's syndrome (HS) is caused by an interruption of the cervical sympathetic pathway to the eye and the face. Acquired HS is mainly caused by benign or malignant neoplasms, and in patients with a history of cancer, it is almost always the result of tumor infiltration into the periphery or the central region of the cervical sympathetic chain. We present the case of a 52-year-old patient with long-term disease-free survival (6 years) after a radical mastectomy for breast cancer who presented with cervicobrachialgia and typical HS due to a left lateral-cervical and supraclavicular lymph nodal mass. Treatment of the metastatic disease with taxanes and concurrent trastuzumab resulted in a complete pain resolution, as well as long-term clinical and radiologic remission; however, the neurological cohort of HS remained as the expression of permanent damage to the sympathetic pathway. This report presents a highly rare case of HS as the first and solitary appearance of metastatic disease in a breast cancer patient. This neurologic involvement should always raise suspicion of metastatic infiltration, and the early recognition of the syndrome may prevent permanent nerve injury.